Habilidades sociais manifestas e auto-reconhecidas: um estudo sobre subjetividade de professores - Hilgenberg, Marissoni do Rocio (2006)
This study aimed to study the social skills of a group of teachers, the manifest ones as well as the ones recognised by the teachers. The theoretical background was based on DEL PRETTE and DEL PRETTE (2001), RODRIGUES (1996) and GONZALEZ REY (2003; 2004). The guiding questions were: How is the teacher building his/her relational knowledge? Which educative sectors are contributing to the developments of teacher’s interpersonal skills? Which social skills are manifested in situations of interpersonal relation? Is there any coherence between the social skills recognised by the teachers and the ones expressed in situations of interpersonal relation? The research was conducted to achieve the following objectives: to identify social spaces which are recognised by teachers as formative spaces of interpersonal relationships; to identify units of subjective sense in the reports of experiences provided by the teachers; to compare the manifest social competencies with the social skills recognised by the teachers. It was a qualitative, phenomenological and interpretative research. The data were collected through a set of questions about the history of teachers' formative process that resulted in interpersonal relationships; report of experience; questionnaire with opened and closed questions. The subjects of this research were seven teachers. The findings of this study showed that: the teacher's knowledge of interpersonal relationships has been achieved through informal and extracurricular means; the factors that contributed to teacher education regarding the interpersonal relationships were: workplace, family, groups of Catholic religion, daily contact with many different people, psychological therapies designed to develop the intrapersonal intelligence; units of subjective sense – how you see yourself, the others and the conflicting situation – produced and expressed by the teachers in their report of experiences, which revealed itself unique and diverse, providing new options for actions and synthesising emotions and meanings that were part of their life history in different moments and in different social spaces. The report of experiences showed that the most evident social skills were self-monitoring and assertiveness and the less evident was empathy. The teachers undertook a selfassessment of their social skills and it confirmed the results of the analysis of the report of experiences, that is the self-monitoring and assertiveness skills are more developed in this group of teachers. However, it revealed some contradictions in relation to the empathy skill since the teachers showed good results in this skill, but it was not evident in the report of experiences. The skill inventory also showed that the teachers who took part in the research believe that their skills to communicate, work, express their positive feelings as well as civility and educational work are well developed. The fact that the teachers engaged in the role of subjects of this study was essential to cross the limits that the conflicting situation seemed to impose and also by the modifications of these limits, which provided options for new directions and future actions. It is possible to conclude that the interpersonal relationships are a complex and contradictory space to constitute and express teacher’s subjectivity.